Perpustakaan Bait Al-Hikmah: Pusat Kegiatan Intelektual pada Masa Dinasti Abbasiyah - Mathar, Muh. Quraisy Mathar (Tumanurung: Jurnal Sejarah dan Budaya, 2024)
The Bait Al-Hikmah Library, or House of Wisdom, is a symbol of the intellectual glory of the Abbasid dynasty, serving as a center of knowledge, translation and research. Founded in Baghdad in the 9th century. This research aims to, firstly, the history of the founding of Bait al-Hikmah, secondly the collection and intellectual activities of Bait al-Hikmah, and thirdly the development of Bait al-Hikmah science. The type of research used is Library Research. The results of this research are, firstly, the establishment of Bait al-Hikmah began with Islam's initial contact with Greek civilization, thus motivating the Abbasid caliphs to absorb and master the scientific civilization obtained from Greece. Both Bait Al-Hikmah have very diverse and valuable collections. This collection includes various types of literature and manuscripts from various scientific disciplines. And thirdly Bait al-Hikmah functions not only as a translation center but also as a library and education center. Therefore, Bait Al-Hikmah remains an important pillar in global intellectual history.